Survival analysis and functional outcome at 6 months in surgical treatment of spontaneous supratentorial intracerebral hemorrhage (ICH) - Ghani, Abdul Rahman Izaini Ghani@Ab (2006)
Objectives. The aim of this study is to evaluate the role of surgery in patients with spontaneous supratentorial intracerebral hemorrhage and to identify predictors of outcome and survival including radiological, genetic, biochemical and treatment factors. Study design and method. This is a prospective cohort study, involving patients with spontaneous supratentorial intracerebral hemorrhage, who fulfill the inclusion criteria for surgical evacuation of the hematoma. This study was conducted over a 13 month period, from February 2004 to March 2005 .Surgery consisted of evacuation of hematoma using craniotomy and microsurgical techniques, as well as in some cases, a decompressive craniectomy. The ventriculostomy for intracranial pressure monitoring and drainage and regional cortical cerebral blood flow (rCoBF) monitoring and microdialysis were performed in all subjects. In addition, the association between Apolipoprotein E (APOE) s4 and outcome was also studied. The study end points were survival time and functional outcome at 6 months based on a dichotomised Glasgow Outcome Scale (GOS). GOS of 1-3 was defined as poor or unfavorable outcome and GOS of 4-5 was defined as good or favorable outcome. The selected clinical, radiological, genetic, biochemical and treatment factors that may influence the survival and functional outcome were analysed for its significance. The univariate analysis of the relation between various variables and GOS at 6 months were analysed using the chi-square test and the survival time was analysed using the Kaplan Meier and log rank test. In multivariate analysis, the binary logistic regression for functional outcome and Cox regression analysis for survival function were performed. Results. 36 patients were recruited into the study during the period of February 2004 and March 2005. All of those were followed-up for a period of 6 months. There were 19 males and 17 females with age ranged from 39 to 76 years and a mean age of 58.6 (±10.1) years and a median age of 61 years. 27(75%) patients had Glasgow Coma Score (GCS) between 5 to 8 on admission and 9(25%) were admitted with GCS of 9 on admission. The survival time ranged from 2 to 180 days with a mean survival time of 105.36 ± 76.4 days. At 6 months, 20 (55.6%) patients had GOS I, 1 (2.8%) patient had GOS II, 10 (27.7%) patients had GOS III and 5 (13.9%) had GOS of IV. None of the patients in this study had GOS ofV. The mortality rate at 6 months was 55%. 86 %had a poor or unfavorable outcome (GOS I-III) and 14% had good or favorable outcome (GOS IV-V). The study of Apolipoprotein E showed that the APOE e4 allele was not detected in all patients. In the univariate analysis for the functional outcome based on GOS, 3 significant variables were identified, the midline shift (p=0.009), regional cortical cerebral blood flow (rCoBF), (p=0.034) and tracheostomy status (p=0.047). The univariate analysis for survival function revealed that the regional cortical cerebral blood flow (rCoBF), (p=0.0143), midline shift (p=0.0064) and pupillary status on admission (p=0.0016) were significant predictors of survival function. The selected variables were then incorporated into models generated by binary logistic regression and Cox regression analysis to identify significant predictors of functional outcome and survival function. Midline shift was the single significant predictor of functional outcome at 6 months (OR=20.8; 95% CI = 1.90- 227.26; p=0.013), and the pupillary status was sole significant predictor of survivalfunction (HR = 2.298; 95% CI 1.168- 4.523; p=0.016). Patients with midline shift> 5mm has almost 21 times higher chances of being associated with poor outcome (GOS I-III) and patients with abnormal pupil on admission has 2.3 times risk of mortality compared to patients with normal pupillary reaction on admission. Conclusion. Surgical treatment for spontaneous intracerebral hemorrhage in this group of patients only benefited a small number of patients in terms of favorable outcome (14%) and in the majority of patients (86% ), the outcome was unfavorable. Patients with midline shift > 5mm has almost 21 times higher chances of being associated with poor outcome (GOS 1-111) at 6 months and patients with an abnormal pupil on admission had an increase in mortality risk of about 2 times compared to patients with normal pupiJJary reaction on admission.